Решение / ответ:
1) 3 (5a - 2b + 4c - 3b) =
= 3 × 5a + 3 × (- 2b) + 3 × 4c + 3 × (- 3b) =
= 15a + (- 6b) + 12c + (- 9b) =
= 15a - 6b + 12c - 9b =
= 15a + 12c + (- 6b - 9b) =
= 15a + 12c + (- 15b) =
= 15a + 12c - 15b.
2) - 12 (- 3a + 2b - c + 5b) =
= - 12 × (- 3a) + (- 12) × 2b + (- 12) × (- c) + (- 12) × 5b = 36a + (- 24b) + 12c + (- 60b) =
= 36a - 24b + 12c - 60b =
= 36a + 12c + (- 24b - 60b) =
= 36a + 12c + (- 84b) =
= 36a + 12c - 84b.
3) (- 4a - 5d + 3c - 2d) (- 4) =
= - 4a × (- 4) + (- 5d) × (- 4) + 3c × (- 4) + (- 2d) × (- 4) = 16a + 20d + (- 12c) + 8d =
= 16a + 20d - 12c + 8d =
= 16a - 12c + (20d + 8d) =
= 16a - 12c + 28d.
Удачи Вам! :)
а) при х = 3,6
3,4 * 3,6 + 5,7 * 3,6 - 4,7 * 3,6 = 12,24 + 20,52 - 16,92 = 15,84
при х = 0,8
3,4 * 0,8 + 5,7 * 0,8 - 4,7 * 0,8 = 2,72 + 4,56 - 3,76 = 3,52
при х = 10
3,4 * 10 + 5,7 * 10 - 4,7 * 10 = 34 + 57 - 47 = 44
б) при х = 2,4
3,8 * 2,4 - (2,8 * 2,4 + 0,7 * 2,4) = 9,12 - (6,72 + 1,68) = 9,12 - 8,4 = 0,72
при х = 8,57
3,8 * 8,57 - (2,8 * 8,57 + 0,7 * 8,57) = 32,566 - ( 23,996 + 5,999) = 32,566 - 29,995 =2,571
в) при х = 0,9
16,75 * 0,9 - (4,75 * 0,9 + 10,8) = 15,075 - (4,275 + 10,8) = 15,075 - 15,075 = 0
при х = 3,01
16,75 * 3,01 - (4,75 * 3,01 + 10,8) = 50,4175 - (14,2975 + 10,8) = 50,4175 - 25,0975 = 25,32